Biogas production and microbial community structure in a stable‐stage of a two‐stage anaerobic digester. Issue 2 (21st October 2019) - García‐Ruíz, María J.; Castellano‐Hinojosa, Antonio; Armato, Caterina; González‐Martínez, Alejandro; González‐López, Jesús; Osorio, Francisco
Abstract: In a pilot plant under the stable‐stage of the two‐stage anaerobic digester, the dynamic of the archaeal, bacterial, and eukaryal community structure was studied as well as their link to performance and biogas production. An effective synergic action between microorganisms was reached since biogas production and particularly methane (CH4 ) generation, were more than two‐times higher in the methanogenic respect to the acidogenic bioreactor. The α‐ and β‐diversity analyses showed that dominant and rare operational taxonomic units of prokaryotic and eukaryotic microorganisms were critical in developing a functional successful anaerobic digestion process. A canonical correspondence analysis showed that acid/alkalinity ratio, volatile fatty acid, and pH parameters mainly affected prokaryotic and eukaryotic phylotypes and a clear positive relationship was found between several phylotypes, such as Methanobacteriaceae, Unknown Thaumarchaeota, Intestinibacter, Coprothermobacter, and Magnoliophyta, with biogas and CH4 production and performance parameters.